Russian intelligence files on Asia. (Leiden, The Netherlands)
1 mikrofilm makarası (576 poz)
Keywords: Geographical, topographical, statistical, ethnographical and hydrographical intelligence : Geographical and topographical intelligence : European and Asian Turkey. Districts and provinces. Towns and fortresses. Statistical and ethnographical intelligence. Intelligence on transportation routes and communications. Highways, mail routes, earth roads, railways, and telegraph lines. Intelligence on transportation routes and communications : Highways, mail routes, earth roads, railways, and telegraph lines. Routes. Hydrographical intelligence. Intelligence on the straits of the Bosporus and the Dardanelles.